Diabetic polyneuropathy, sensory neurons, nuclear structure and spliceosome alterations: a role for CWC22 - Kobayashi, Masaki (Dis Model Mech, 2017)
Unique deficits in the function of adult sensory neurons as part of their early neurodegeneration might account for progressive polyneuropathy during chronic diabetes mellitus. Here, we provide structural and functional evidence for aberrant pre-mRNA splicing in a chronic type 1 model of experimental diabetic polyneuropathy (DPN). Cajal bodies (CBs), unique nuclear substructures involved in RNA splicing, increased in number in diabetic sensory neurons, but their expected colocalization with survival motor neuron (SMN) proteins was reduced – a mislocalization described in motor neurons of spinal muscular atrophy. Small nuclear ribonucleoprotein particles (snRNPs), also participants in the spliceosome, had abnormal multiple nuclear foci unassociated with CBs, and their associated snRNAs were reduced. CWC22, a key spliceosome protein, was aberrantly upregulated in diabetic dorsal root ganglia (DRG), and impaired neuronal function. CWC22 attenuated sensory neuron plasticity, with knockdown in vitro enhancing their neurite outgrowth. Further, axonal delivery of CWC22 siRNA unilaterally to locally knock down the aberrant protein in diabetic nerves improved aspects of sensory function in diabetic mice. Collectively, our findings identify subtle but significant alterations in spliceosome structure and function, including dysregulated CBs and CWC22 overexpression, in diabetic sensory neurons that offer new ideas regarding diabetic sensory neurodegeneration in polyneuropathy.